Al-Maslahah dalam Pandangan ‎ al-Ghazaly, al-Shatiby dan al-Tufy - Abu Azam Al Hadi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
Al-Maslahah is merely an effort to gain benefit as well as prevent harm for the sake of human welfare in this world without considering its compliance with the purpose of shari’ah which are the preservation of religion, life, consciousness, family, and property. However, there are three contradictory opinions concerning establishing Al-Maslahah as a source of islamic law. A group od islamic legal theorists tend to limit the use of Al-Maslahah such as al-Ghazaly, while the second group tend to employ it moderately such as al-Shatiby. The last group is those group who employ it exclusively without pay much attention to the textual reference as promoted by al-Tufy. Surprisingly, there is a common ground between the three opinions. The first is that al-maslahah should not merely be based on human desire, but it has to be in accordance to fundamental goal of islamic law. The second is that al-maslahah should be a fundamental of generating benetif and preventing harm.